1990
DOI: 10.1055/s-2007-999462
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Fibronectin and Prostacyclin Metabolite in Peripartum Preeclamptic Women

Abstract: Plasma fibronectin and prostacyclin levels have been reported to vary in preeclamptic women when compared with pregnant control women. Elevation of fibronectin and deficiency of prostacyclin have been postulated to be due to endothelial cell disruption or dysfunction. Eighteen preeclamptic women and 19 normal pregnant controls were evaluated for plasma levels of fibronectin and the prostacyclin metabolite 6-keto-prostaglandin F1 alpha (6-keto-PGF1 alpha). 6-keto-PGF1 alpha and fibronectin plasma levels in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1992
1992
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…SHAKLIN and SIBAI [21] by electron-microscopy and ROBERTS et al [24,25] by serum of preeclamptic patients in-vivo and in-vitro proved that endothelial cell damage is the basic pathology in pregnancy induced hypertension. Fibronectin as a marker of endothelial cell injury has been shown to be high in pregnancy induced hypertension [2,4,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SHAKLIN and SIBAI [21] by electron-microscopy and ROBERTS et al [24,25] by serum of preeclamptic patients in-vivo and in-vitro proved that endothelial cell damage is the basic pathology in pregnancy induced hypertension. Fibronectin as a marker of endothelial cell injury has been shown to be high in pregnancy induced hypertension [2,4,20].…”
Section: Discussionmentioning
confidence: 99%
“…Dies konnten Shaklin und Sibai [21] elektronenmikroskopisch und Roberts et al [24,25] im Serum von präe-klamptischen Patientinnen in vivo und in vitro zeigen. Es wurde nachgewiesen, daß das Fibronectin als Marker der Verletzung der Endothelzelle beim schwangerschaftsinduzierten Hypertonus erhöht ist [2,4,20]. Auch wir fanden erhöhte Fibronectinspiegel.…”
Section: Zusammenfassung Aussagekraft Von Antithrombin-iii-und Fibronunclassified
See 1 more Smart Citation
“…Watson et al [75] found that eclamptic patients have depressed PGI2 levels; whereas serum from MgS04-treated eclamptic patients increased release of PGI2 by cultured (human umbilical vein) endothelial cells and it overcame thrombin induced-platelet adhesion to endothelium. Calvin et al [118] found that plasma fibro nectin, released from damaged endothelium, was higher in 18 preeclamptic women than in 19 normal pregnant con trols. However, the metabolite of PGI2, 6-keto-PGFlx which they suggested is possibly a poor index of PGI2 at the microvascular level was also higher.…”
Section: Magnesium Platelet Aggregation and Prostanoids Of Toxemias mentioning
confidence: 98%